Pengaruh Model Pembelajaran Jigsaw dan Teams Games Tournament Terhadap Karakter Kepedulian Sosial dan Kejujuran dalam Pendidikan Jasmani Olahraga Kesehatan - Wardana, Achmad; Priambodo, Anung; Pramono, Made (JOSSAE (Journal of Sport Science and Education), 2020)
Abstract This study generally aims to reveal differences in the level of characters social caring and honesty based on gender resulting from learning physical sports and health educarion (PJOK) through the treatment of Jigsaw learning models and teams games tournament. This research method is an experimental research with 2x2 factorial design. The instrument used was a questionnaire character of social caring and honesty that had been validated and filled out by students who took part in the research program. Data collected in the form of pretest and posttest results were processed with SPSS 20 using a twoway-anova factorial analysis test. The results of the study can be concluded that (1) there is no differnce in the level of social caring characters from the treatment of Jigsaw learning models and teams games tournament in PJOK learning, (2) there is no difference in the level of social caring character based on gender in learning PJOK, (3) there is a differnce in the level of honesty character from the treatment of Jigsaw learning models and teams games tournament in PJOK learning, (4) there is no differnce in the level of honesty character based on gender in PJOK learning.